Analisis Jual Beli Golok Dengan Cara Panjar menurut Perspektif Ekonomi Syariah di PG. Binangkit Cibeureum Tanjungsiang Subang - Abdul Abdul Hopid; Jalaludin jalaludin; Ahmad Damiri (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2021)
In Islam, muamalah is a form of convenience for humans to fulfill everything related to their daily needs as living beings and social beings, among the actions of the community to meet material needs is buying and selling with a down payment system, but some people still do not understand about the practice of buying and selling with a down payment system in a sharia economic perspective. This study aims to determine the sale and purchase of the down payment system according to the experts, and to find out the sharia economic review of buying and selling machetes in PG. Binangkit Cibeureum Tanjungsiang Subang. This research is a type of qualitative research with an empirical approach, the data collection techniques used are observation, interviews, and documentation. In this study, the data sources consist of primary data, namely PG managers and owners. Binangkit Kp. Cibeureum Tanjungsiang-Subang and secondary data in the form of records or archives in PG. Raise. Regarding jaul-buying using the Jurisprudence system, As-Syafi'i is of the opinion that it is invalid, based on the hadith narrated by Amru bin Shuaib which reads, "From Amru bin Shu'aib, his father and grandfather were pleased with Allah, so the Prophet said: The Prophet forbade selling- buy 'urban' (Narrated by Abu Dawud)". The understanding of As-Shafi'i fiqh is to avoid the contents of the content of Surah an-Nisa verse 29. Which reads. "O you who believe, do not eat each other's property in a vanity way, except by means of commerce, which prevails consensual among you. and do not kill yourself. Indeed, Allah is Most Merciful to you.” While the Hanbali fiqh understanding of the sale and purchase of advances is of the opinion that the sale and purchase is valid. Based on the Hadith narrated by Zaid bin Aslam and Atsar companions or the practice of the Prophet's companions, namely Umar who bought the prison building to Safwan bin Ummayyah. "The Messenger of Allah was asked about buying and selling the 'urbun system, and he allowed it." Opinions closely related in PG. Binangkit Cibeureum Tanjungsiang regarding the implementation of buying and selling machetes with a down payment system is the opinion of Hanbali fiqh where the practice of buying and selling machetes using down payment is due to the buying and selling that occurs in PG. Binangkit Cibeureum Tanjungsiang is allowed because this is to ensure the continuity of the transaction and guard against buying and selling machetes. Furthermore, a review of Islamic economics based on the results of the researcher's analysis, the sale and purchase of machetes both with the down payment system and directly in the PG. Binangkit is in accordance with sharia both from the provisions related to sighat al-aqd, the parties to the contract, Muthman/mabi '(Object), and the provisions related to Tsaman or the price